Influence Of External Shading Devices On Daylight Availability In South-Facing Classrooms In The Tropics (International Journal of Environmental Sciences, 2025)
Adequate daylighting is a vital element of effective learning environments, profoundly affecting students' visual comfort, cognitive performance, and psychological well-being. Insufficient access to natural light not only hampers academic productivity but can also negatively impact the physical and mental health of occupants. In tropical climates such as Chittagong, Bangladesh, the design of educational buildings must strike a careful balance between daylight access and thermal comfort. While external shading devices play a crucial role in minimizing solar heat gain and glare, they can also obstruct daylight entry, potentially diminishing indoor lighting quality. This study explores how different configurations of external shading devices influence daylight performance in south-facing classrooms, using a typical classroom at the Chittagong University of Engineering and Technology (CUET) as a case study.A mixed-method approach was adopted, integrating on-site illuminance measurements with daylight simulation tools to evaluate the effectiveness of the existing shading strategies. Alternative shading configurations were subsequently proposed and analyzed to assess their impact on indoor daylight distribution. The findings indicate that carefully optimized shading geometries can enhance daylight penetration while maintaining acceptable thermal comfort levels, thus improving overall indoor environmental quality. This research provides evidence-based design recommendations for the integration of passive shading solutions in classroom architecture, aiming to assist architects and designers in creating sustainable, energy-efficient educational environments that support both visual comfort and occupant well-being in tropical regions.